Synthesis of Polysubstituted Symmetrical BODIPYs via Fischer Carbene Complexes: Theoretical, Photophysical and Electrochemical Evaluation. Issue 71 (26th October 2022) - Vázquez, Juan Luis; Velazco‐Cabral, Ivan; Flores‐Álamo, Marcos; Turlakov, Gleb; Rodríguez, Geraldina; Moggio, Ivana; Arias, Eduardo; Peña‐Cabrera, Eduardo; Vázquez, Miguel A.
Abstract: A series of new symmetrical highly substituted BODIPYs 6 a –l was synthesized through a prefunctionalization approach in 35 %–89 % yields from the pyrrole core. This strategy allowed modulation of the substituents at the different positions based on the choice of Fischer's alkynyl carbenes, oxazolones and aldehydes used as precursors. The substituent variation at positions 2, 6, 3 and 5 had the greatest effect on the modulation of their photophysical properties such as absorption ( λ abs ) and emission ( λ em ) wavelengths, extinction coefficient ( ϵ ), quantum yields ( ϕ ), Stokes shifts (Δ ν ), fluorescence decay, radiative ( k rad ) and non‐radiative ( k nr ) constants and the CIE 1931 coordinates. Theoretical calculations allowed to corroborate the effect of the substituents of meso ‐position on the modification of the dihedral angles. Cyclic voltammetry studies revealed that the BODIPY series presents similar redox potential behavior, being electrochemically active even in successive cycles, which suggests that transport by diffusion is the dominant process. Abstract : Pyrrole polyfunctionalized core is obtained from Fischer alkynyl carbenes and oxazolones and used to obtain highly functionalized symmetric BODIPYs with modulating optoelectronic properties.